Analisis Distribusi Estimasi Kadar PM10 dan CO di Kota Padang Tahun 2015 dan 2025 - Tri Raisya Nur Salsabila; Widya Prarikeslan (Al-DYAS, 2026)
Air pollution is one of the important environmental issues because it has broad impacts on public health and environmental quality, especially in urban areas experiencing increased transportation activity and urbanization, such as Padang City. This study aims to analyze the distribution of estimated PM₁₀ and CO levels in 2015 and 2025 and to identify their spatial-temporal changes. This study used a quantitative approach through estimation modeling based on Landsat 8 OLI/TIRS Collection 2 Level 2 imagery data. The results showed that the estimated distribution of PM₁₀ in Padang City was in the good category according to the Air Pollution Standard Index (ISPU), with an average concentration of 23.78 µg/m³ in 2015 and 24.18 µg/m³ in 2025. Meanwhile, the distribution of CO concentration was in the moderate category, with an average of 83.61 µg/m³ in 2015 and 83.62 µg/m³ in 2025. Spatial-temporal analysis showed a decreasing trend in PM₁₀ concentration, whereas CO concentration tended not to experience significant spatial or temporal changes. These findings emphasize the importance of satellite imagery-based air quality monitoring as a supporting basis for formulating air pollution control policies in Padang City.